If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4a + -6 = -36 Reorder the terms: -6 + 4a = -36 Solving -6 + 4a = -36 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 4a = -36 + 6 Combine like terms: -6 + 6 = 0 0 + 4a = -36 + 6 4a = -36 + 6 Combine like terms: -36 + 6 = -30 4a = -30 Divide each side by '4'. a = -7.5 Simplifying a = -7.5
| 21x+6=17x+32 | | 2(w+3)+2w=42 | | 6(4-2h)=4(5-3h) | | 3y+9= | | -9(d+2)=4(15+d) | | 90+x=125 | | -2(16-3p)=-5p+1 | | 2-y=1 | | -50t-5=70 | | 6-9= | | 80+x=95 | | X-0=1 | | -11x-3x=10-10x | | 3(-z+12)=4(z-5) | | 2x-5+3x=5 | | 5-6x=3(1-2x) | | 3n+6=87 | | Z^2-20z-21=0 | | 5y=3(y-2) | | -21=-5v+3(v-5) | | 3b+16=40 | | -16-9-4x=-9 | | =1+1 | | 8x+20=2x+20 | | -5=6n | | 5-3x+2=4x+7 | | 4x^2-23x+13=-7x+6 | | 24-6m=0 | | .5(10z+8)-2=4(z-6) | | 8+9x=-6 | | 2(x+3)=5+2x | | x/3+4=x/6+2 |